EFL STUDENTS’ ATTITUDE TOWARDS RESEARCH PAPER WRITING FOR PUBLICATION - Nabila, Lia; Hartono, Hartono; Maharani, Mega Mulianing; Widiyati, Elok; Hidayati, Nani; Bakhtiar, Muhamad Rifqi (STKIP Persada Khatulistiwa Sintang, 2025)
Many Indonesian undergraduate programs have recently required their students to publish research papers before graduation. However, for some students, this requirement is not easy to meet, especially for students of the English education study program, whose papers must be written in English. This study aims to: 1) describe the attitude of the English education study program students towards English research paper writing for publications, and 2) identify possible factors affecting their attitude. Sixty-five students of the English Education Study Program from the English department of three universities in Semarang, Central Java, were selected conveniently and participated in the study as respondents. Data on the attitude were collected using a Likert-type questionnaire and analyzed quantitatively, while data on factors affecting attitude were collected through interviews and analyzed qualitatively. The results show that students have positive attitude, although they face problems related to language mastery. In a five-point scale measurement, most of the statement mean scores are above 3.0 for positive statements, and below 3.0 for the negative statements. The results reveal that students are aware of the potential advantages linked to English research paper writing and publication, such as increasing knowledge and language mastery, improving academic performance, etc.. However, the findings also show that students face challenges related to limited vocabulary, grammar structure, and sentence constructions. Implications of the study are presented, and future research directions are offered.